WAYS TO IMPROVE THE EPIDEMIOLOGICAL SURVEILLANCE AND CONTROL OF ANTHRAX IN THE RUSSIAN FEDERATION - A. Yu. Popova; E. B. Ezhlova; Yu. V. Demina; A. N. Kulichenko; A. G. Ryazanova; N. P. Buravtseva; E. I. Eremenko; I. А. Dyatlov; V. V. Maleev; E. G. Simonova; S. A. Каrtavaya; I. G. Karnaukhov; et al. (Проблемы особо опасных инфекций, 2017)
Presented are summarized data on anthrax epidemiological and epizootiological situation in the Russian Federation. The causes of the unstable situation are analyzed. Characterized are modern clinical and epidemiological features of anthrax infection, as well as key areas for improvement of surveillance and control of anthrax in the current conditions based on a systematic approach and effective interdepartmental cooperation.